Answer:
0
Step-by-step explanation:
7x + -2z = 4 + -1xy
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add 'xy' to each side of the equation.
7x + xy + -2z = 4 + -1xy + xy
Combine like terms: -1xy + xy = 0
7x + xy + -2z = 4 + 0
7x + xy + -2z = 4
Add '2z' to each side of the equation.
7x + xy + -2z + 2z = 4 + 2z
Combine like terms: -2z + 2z = 0
7x + xy + 0 = 4 + 2z
7x + xy = 4 + 2z
Reorder the terms:
-4 + 7x + xy + -2z = 4 + 2z + -4 + -2z
Reorder the terms:
-4 + 7x + xy + -2z = 4 + -4 + 2z + -2z
Combine like terms: 4 + -4 = 0
-4 + 7x + xy + -2z = 0 + 2z + -2z
-4 + 7x + xy + -2z = 2z + -2z
Combine like terms: 2z + -2z = 0
-4 + 7x + xy + -2z = 0
Answer:
48
Step-by-step explanation:
The square pyramid has exactly the same four triangles.
In order to find the whole surface area, we must find the area of one of the triangles and multiply them by 4.
Surface area of square pyramid = 
Where we know that b = 4 and h = 6.
Substituting into the formula should give us the answer 48.
Answer:
B x=2 y=6
Step-by-step explanation:
For ABCD to be parallelogram, following conditions should be satisfied:
2x - 0 = x + 2 & 4y - 8 = y + 10
2x - 0 = x + 2
2x - x = 2
x = 2
4y - 8 = y + 10
4y - y = 10 + 8
3y = 18
y = 18/3
y = 6
If the pre-image is on the left, then it moves to the right and up to transform into the new image (diagonal pointed to the upper right).
If the pre-image is on the rightt, then it moves to the left and down to transform into the new image (diagonal pointed to the lower left).
Answer: A and F
Answer:
4000 grams
Step-by-step explanation:
Volumes of similar figures are proportional to the cube of their linear dimensions. Areas are proportional to the squares of their linear dimensions.
Given an area ratio, the ratio of linear dimensions will be the square root of it, or the 1/2 power of the ratio of areas. Then the volume ratio will be the cube of the ratio of linear dimensions or ...
volume ratio = ((area ratio)^(1/2))^3 = (area ratio)^(3/2)
Here, the mass of the smaller object will be proportional to its volume, which, in turn, is proportional to the mass of the larger object times the 3/2 power of the area ratio. So, the mass of object A is ...
((28 cm^2)/(40.32 cm^2))^(3/2) × (6912 grams) = 4000 grams